Complement factor H mutations and gene polymorphisms in haemolytic uraemic syndrome: the C-257T, the A2089G and the G2881T polymorphisms are strongly associated with the disease - Caprioli, Jessica; Castelletti, Federica; Bucchioni, Sara; Bettinaglio, Paola; Bresin, Elena; Pianetti, Gaia; Gamba, Sara; Brioschi, Simona; Daina, Erica; Remuzzi, Giuseppe; Noris, Marina (Human molecular genetics, 2003)
Mutations in complement factor H (HF1) gene have been reported in non-Shiga toxin-associated and diarrhoea-negative haemolytic uraemic syndrome (D−HUS). We analysed the complete HF1 in 101 patients with HUS, in 32 with thrombotic thrombocytopenic purpura (TTP) and in 106 controls to evaluate the frequency of HF1 mutations, the clinical outcome in mutation and non-mutation carriers and the role of HF1 polymorphisms in the predisposition to HUS. We found 17 HF1 mutations (16 heterozygous, one homozygous) in 33 HUS patients. Thirteen mutations were located in exons XXII and XXIII. No TTP patient carried HF1 mutations. The disease manifested earlier and the mortality rate was higher in mutation carriers than in non-carriers. Kidney transplants invariably failed for disease recurrences in patients with HF1 mutations, while in non-mutated patients half of the grafts were functioning after 1 year. Three HF1 polymorphic variants were strongly associated with D−HUS: -257T (promoter region), 2089G (exonXIV, silent) and 2881T (963Asp, SCR16). The association was stronger in patients without HF1 mutations. Two or three disease-associated variants led to a higher risk of HUS than a single one. Analysis of available relatives of mutated patients revealed a penetrance of 50%. In 5/9 families the proband inherited the mutation from one parent and two disease-associated variants from the other, while unaffected carriers inherited the protective variants. In conclusion HF1 mutations are frequent in patients with D−HUS (24%). Common polymorphisms of HF1 may contribute to D−HUS manifestation in subjects with and without HF1 mutations.